DEVELOPMENT OF A CROSS-PLATFORM SYSTEM FOR PERSONAL FINANCIAL ANALYSIS USING THE FLUTTER FRAMEWORK - SEVERYNENKO, DANYLO; SENYK, ANDRIY; PUKACH, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In today's fast-paced world, characterized by diverse spending opportunities, numerous subscriptions, and aggressive advertising, people frequently find themselves unaware of where their money is being lost. Although there are various financial management apps available in the market, most of them have flaws, particularly when it comes to the Ukrainian market. Given this information, it becomes evident that the development of an application that effectively assists individuals in managing their personal finances is crucial.This paper provides an overview of specialized information sources focused on personal finance accounting and financial advice. It evaluates the pros and cons of different applications. Through this analysis, it becomes apparent that the majority of popular apps are designed for the US market, with over half of them being paid systems. Consequently, the development of a cross-platform financial analysis system requires careful selection of technologies suitable for this application. The current world of information technology offers a wide range of programming languages, libraries, and frameworks that can help address various problems.The paper further presents a comparative analysis of specific information technologies and programming languages, such as Python, Flutter, Node.js, and others, that can be employed in financial analysis and consulting. Based on the aforementioned data, a specific technology stack was chosen to create a cross-platform system for personal financial analysis. Additionally, the paper documents the process of developing the desired application, resulting in a finished product that functions as a mobile Android application, web-oriented system, and desktop Windows application. In conclusion, the efforts described in this work have led to the successful creation of a cross-platform application for personal financial analysis.
Keywords: Cross-platform; finances; Dart; Flutter; web development